2021
DOI: 10.1186/s40644-021-00420-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor stiffness measured by 3D magnetic resonance elastography can help predict the aggressiveness of endometrial carcinoma: preliminary findings

Abstract: Background Preoperative evaluation of aggressiveness, including tumor histological subtype, grade of differentiation, Federation International of Gynecology and Obstetrics (FIGO) stage, and depth of myometrial invasion, is significant for treatment planning and prognosis in endometrial carcinoma (EC). The purpose of this study was to evaluate whether three-dimensional (3D) magnetic resonance elastography (MRE) can help predict the aggressiveness of EC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Factors contributing to these benefits include 3D laparoscopy's ability to offer surgeons a three-dimensional viewpoint, enhancing tissue structure differentiation and meticulous operation, Facilitating direct lesion site identification, allowing comprehensive cancerous tissue and metastatic lymphocyte removal, and Assisting precise adhesion differentiation between the lesion and adjacent tissues, preventing cancer cell proliferation and limiting damage to surrounding structures. 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…Factors contributing to these benefits include 3D laparoscopy's ability to offer surgeons a three-dimensional viewpoint, enhancing tissue structure differentiation and meticulous operation, Facilitating direct lesion site identification, allowing comprehensive cancerous tissue and metastatic lymphocyte removal, and Assisting precise adhesion differentiation between the lesion and adjacent tissues, preventing cancer cell proliferation and limiting damage to surrounding structures. 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have also suggested that matrix stiffness plays an important role in the prediction of aggressiveness and affects the morphology, drug sensitivity and mechanical properties of cervical cancer cells [69][70][71] . It can therefore be stated that treatment with anti-LCN2 antibody decreased the stiffness of the tumor, thus helping in tumor regression.…”
Section: Discussionmentioning
confidence: 99%
“…Its ability to provide quantitative measurements of tissue properties opens up new possibilities for diagnosing and monitoring various pathologies and diseases. These potential applications of MRE are supported by evidence demonstrating excellent reproducibility and repeatability [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 85%